Efficacy of CyberKnife Stereotactic Radiosurgery in Treating Trigeminal Neuralgia: A Single-Institution Study - Sreenath, Nihanthy D.; Potharaju, Mahadev; Chandrasekar, Sanjay; Mangaleswaran, Balamurugan (Indian Journal of Neurosurgery, 2025)
Trigeminal neuralgia (TN) is a chronic facial pain disorder. While medications like analgesics and antiepileptics are first-line treatments, some patients may require surgical options like microvascular decompression or rhizotomies, which carry neurological risks. CyberKnife frameless stereotactic radiosurgery (CK SRS) offers a noninvasive, effective alternative with fewer side effects.In our study, 30 patients with unilateral TN (VAS [visual analog scale] score > 5) were treated. Using computed tomography and magnetic resonance imaging, a 5 to 6 mm segment of the trigeminal nerve, located 2 to 3 mm distal to the brainstem's dorsal root entry zone, was targeted. A 60 Gy dose, prescribed to a median isodose of 85%, was delivered for radiosurgical rhizotomy.Patients were followed for a median of 48 months. Of the 30 patients, 21 achieved satisfactory pain relief (VAS ≤ 3), with pain relief occurring at varying intervals, and 9 patients had partial relief (VAS > 3) and remained on medication. One patient had a recurrence pain and was re-irradiated at 36 months. Ten patients developed facial numbness, assessed using the Barrow Neurological Institute Facial Numbness Scale score, with a latency period of 10 months. All patients were on carbamazepine, gabapentin, and mecobalamin until pain relief was achieved.The nearly 70% success rate after SRS is comparable to or better than other treatment modalities for TN. Nonisocentric CyberKnife SRS proves to be a safe and effective option for managing TN.
Keywords: trigeminal neuralgia; CyberKnife; nonisocentric; radiosurgery; rhizotomy